URGENSI PENDIDIKAN KEWIRAUSAHAAN DI KALANGAN MAHASISWA PTKI - Zubaedi, Zubaedi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
The Urgency of Entrepreneurial Education among Students in PTKI. This paper describes the reasonsfor the importance of entrepreneurial education in PTKI. This article assumes that entrepreneurial education willencourage students of PTKI to begin to recognize and open a business or entrepreneurship. Those who have anorientation to be employees should be changed to find jobs. Entrepreneurship- minded education is characterizedby applying the principles and methodologies towards developing life skills for learners through an integratedcurriculum developed in PTKI. Entrepreneurs have characteristics such as spirit of achievement, busy to look foropportunities, think big and whole, sharp intuition in business, bold and ready to take risks, tolerance of ambiguity,optimistic and hurry to improve, rapidly count and make decision, and encourage to be more prosperous.